Ubuntu as a Normative Ethic of Empowerment: A Philosophical Critique of Faith-Based Vocational Training in a Pentecostal Church - Zhakata, Revi; Wuta, Rodwell Kumbirai (Philosophy and Realistic Reflection, 2025)
This paper explores Ubuntu as a normative ethic to critically assess empowerment claims in a Pentecostal vocational training program in Chitungwiza, Zimbabwe. As Pentecostalism influences socio-economic development across Africa, it raises ethical questions about alignment with indigenous African values. Ubuntu, rooted in relationality, communal solidarity, and dignity, offers a culturally grounded framework for evaluating faith-based development initiatives. Through philosophical critique and qualitative data from pastors, trainees, and church members, the study reveals that while the program promotes empowerment, centralised leadership, limited participatory governance, and emphasis on material prosperity often undermine Ubuntu’s holistic vision of empowerment. The initiative reflects Ubuntu’s communal ethics in social support but struggles with power imbalances and narrow economic success metrics. The analysis further demonstrates that empowerment framed solely through prosperity theology risks marginalising vulnerable groups, particularly women and youth, who may lack equal access to decision-making structures. Moreover, the program’s vocational focus, while beneficial for short-term livelihood generation, does not sufficiently integrate spiritual, ethical, and communal dimensions that Ubuntu considers vital for human flourishing. The paper argues for inclusive governance, integrative empowerment encompassing spiritual, social, and economic dimensions, and critical theological reflection to harmonise Pentecostalism with Ubuntu ethics. Integrating Ubuntu into development ethics contributes to decolonising empowerment frameworks and offers a robust foundation for culturally relevant, ethically sound community upliftment models in Africa. Ultimately, the study contends that integrating Ubuntu into development ethics not only contributes to decolonising empowerment frameworks but also strengthens the legitimacy, sustainability, and cultural resonance of faith-based interventions in Africa.